The relationship between whole blood iron and fasting blood glucose in community-dwelling elderly people: a cross-sectional study - Shu-Zi-Qi Chen; Rou-Jun Pan; Meng-Yan Sun; Lian-Ping He; Cui-Ping Li (Journal of Health, Population and Nutrition)
Abstract Iron overload increases fasting blood glucose level in mice, leading to insulin insensitivity. However, no such relationship has been shown in the population. The relationship between whole blood iron levels and fasting blood glucose levels remained unclear. This study aimed to determine whether whole blood iron levels were associated with fasting blood glucose levels in community-dwelling older adults. This cross-sectional study was based on a community population and analyzed the distribution of whole blood iron and fasting blood glucose in a community population. A sample of 1560 community residents had their fasting blood glucose, gender, and age measured during the study. Covariates were assessed using correlation analysis, partial correlation analysis, and Student’s t-test. To further investigate the impact of confounding factors in this study, we compared variations in whole blood iron levels between genders. Pearson correlation analysis showed no correlation between whole blood iron and fasting blood glucose. After adjusting for age and gender, no correlation was found between whole blood iron and fasting blood glucose as well. However, Pearson correlation analysis showed a correlation between whole blood iron and age(P<0.05, r=-0.181). whole blood iron concentrations gradually decreased with age. At the same time, mean whole blood iron concentrations were lower 420 mg/l among women and men in the community. And the mean levels of whole blood iron were higher in men(504.08 mg/l ± 45.98 mg/l) than in women(453.80 mg/l ± 38.13 mg/l). Our study indicated no association between whole blood iron. Age was a covariate, but fasting blood glucose was not, and fasting blood glucose was independently associated with whole blood iron concentrations, suggesting that older women in this community need adequate iron supplementation.